SISTEM EKONOMI KERAKYATAN SEBAGAI LANDASAN PEMBANGUNAN EKONOMI INDONESIA MELALUI UKM, KOPERASI DAN PEMERINTAH DAERAH - sabil sabil (Universitas Bina Sarana Informatika, 2014)
Democratic economic system has been defeated by libral economic system that controls almost all countries, whereas in Indonesia has long been known that a community-based economic system in which due regard to the culture of a nation of Indonesia. Economic Democracy is taken from the values of the Indonesian nation, democratic economic system in effect since 1998, then the government was determined to implement a democratic economic system with MPR decree issued No.IV/MPR/1999, of the Guidelines which states that Indonesia's economic system is a system of social economy. Populist oriented development and a wide range of discretion in favor of the interests of the people. people's economy developed as an effort to further promote the community. In other words, the concept of people's economy performed as a strategy for build more priority to the welfare of the community empowerment. people's economy can be realized by restructuring the political institutions at district level. Thus the question of the economic development of the people can not be separated from the political institutions at district level. For it must create a political climate that is conducive to the economic development of the people. SMEs, cooperatives, local and central government, Food security is a crutch goes some populist economic activity in Indonesia, when the economic crisis hit Indonesia a monster companies are experiencing the fall as well as many out of business, while SMEs and cooperatives remained robust even exist at the time that Keywords : Democratic economy system, UKM, Cooperative